Utero-Tubal Insufflation Technique for diagnosis of Tubal Impatency in cows - Athman KV (Department of Animal Reproduction, College of Veterinary and Animal Sciences, 1981)
The objective of the present study was to design an apparatus for utero-tubal insufflation test and to standardize its use in both excised genitalia and in live animals for the diagnosis and treatment of tubal impotency. Perfect obturation of the cervix was obstained using a stainless steel catheter with 22 FR. Neo Foley’s latex catheter sleeved over. Unilateral and bilateral impotency were recorded in 8.70 and 19.25 per cent of the excised genitalia. The incidence of unilateral and bilateral impotency in 37 infertile animals were found to be 2.70 and 13.52 per cent respectively. The mean pressure at which air escaped from both the tubes in excised genitalia was 128.12 mm. Hg. In cows and 148.93 mm. Hg. In heifers. On the contrary in experimental animals the corresponding pressure in cows and heifers were 116.38 mm. Hg. And 127.50 mm. Hg. Respectively. It was observed that a higher pressure was required to open both the tubes in heifers than in cows. Blown up condition of the uterus took place in excised genitalia of cows and heifers between 100-280 mm. Hg. And 100-260 mm. Hg. Respectively. The pressure range for producing “blown up” condition in experimental animal was found to be 120-220 mm. Hg. In cows and 195-200 mm. Hg. In heifers. Since the safety margin was estimated to be 60.00 mm. Hg. In experimental cows, the test is considered to be a safe diagnostic test for tubal impotency. Although uterus might be “blown up” in a very few cases at a pressure lower than the higher pressure for escape of air from normally patent tubes, the test will not endanger the life of the animal. Since 69.56 percentage of cows with bilateral patency of salpinx on testing conceived after insemination, utero-tubal insufflation test could also be exploited for the treatment of temporary tubal blockage.